A zeolite-kaolin composite hemostatic gauze and preparation method thereof
By applying a kaolin-self-adhesive mixed coating on flexible zeolite gauze, the problems of high shedding rate of zeolite hemostatic gauze powder and large amount of adhesive are solved, and efficient, safe and portable hemostatic materials are achieved, which improves the Chemical stability and biosafety of the product.
Patent Information
- Application Number
- CN202411368613.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2024-08-30
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-29
AI Technical Summary
The existing zeolite hemostatic gauze has a high powder shedding rate during use, which affects the safety and storage stability of the product. The excessive amount of binder used leads to a decrease in biosafety, which cannot meet the ideal hemostatic performance and portability. Require.
Use a flexible zeolite gauze grown in situ to coat kaolin-self-adhesive mixed coating, connect zeolite to the gauze substrate through covalent bonds, reduce the amount of binder used, and adjust the binder through aqueous polymer latex dilution The glass transition temperature and particle size are formed to form a stable self-adhesive coating to improve the bonding effect.
It significantly reduces the powder shedding rate, improves hemostasis efficiency and the chemical stability of the product, extends the shelf life, enhances biosafety and convenience of use, and meets the requirements of efficient, safe and portable hemostasis materials.
Smart Images

Figure CN118873717B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical material preparation, and in particular relates to a zeolite-kaolin composite hemostatic gauze and a preparation method thereof. Background Art
[0002] Hemorrhagic shock caused by massive bleeding is the most common and preventable cause of death in all types of trauma. If hemostasis can be achieved quickly and in a timely manner, a large number of lives that might otherwise die from excessive bleeding can be saved. Hemostatic drugs and hemostatic materials are basic tools for controlling bleeding in modern medical practice and are widely used in pre-hospital emergency and surgical environments. The development of more efficient and safe rapid hemostatic materials is a goal that the academic and industrial communities have been pursuing. Ideal rapid hemostatic materials should have the following characteristics in order of importance: (1) High efficiency: they can quickly achieve hemostasis and have good and effective hemostatic ability for severe bleeding conditions such as arterial bleeding; (2) Easy operation: they can be used correctly and immediately by non-professionals even if they are not in a medical institution; (3) Portability: the product is stable and easy to store for a long time and is easy to carry. It does not require constant temperature or low temperature storage and can withstand various outdoor weather conditions; (4) Safety: it can be easily removed after hemostasis is completed, and will not leave harmful residues on the wound surface, and will not damage tissues and organs due to heat release and other reasons; (5) Biosafety: it has good biocompatibility, is non-carcinogenic, non-teratogenic, non-sensitizing, non-toxic and has no side effects. However, there is currently no hemostatic product that can fully meet all of the above requirements under harsh combat and accident conditions.
[0003] A large number of natural and artificial organic polymer materials such as absorbent cotton gauze, cotton balls, oxidized cellulose, gelatin sponges, chitosan products, and polyvinyl alcohol sponges are widely used in application scenarios of minor bleeding. However, they are not effective in severe bleeding scenarios such as femoral arteries and carotid arteries, and do not meet the most important high efficiency requirements of ideal emergency hemostatic materials. Biological hemostatic materials represented by fibrin glue composed of fibrinogen and thrombin have a high hemostatic effect. However, the high production cost, strict storage requirements, and complex usage guidelines limit them to being only used by professionals in professional medical environments such as hospitals, which does not meet the requirements of ease of operation and portability. Inorganic mineral materials such as zeolites, kaolin, montmorillonite, mesoporous silica, bioglass, and transition metal oxides newly discovered in recent decades also have good procoagulant effects, especially various zeolites, kaolin and montmorillonite in clay, which can achieve rapid hemostasis of arterial bleeding. At the same time, this type of inorganic mineral material has a stable chemical composition, can be stored for a long time in a wide range of temperature and humidity, and has excellent weather resistance. It is also relatively easy to use. Simply contacting the powder with the bleeding area can promote blood coagulation. It has the high efficiency, ease of operation and convenience requirements of an ideal hemostatic material.
[0004] However, in the early days, such inorganic mineral hemostatic materials were in powder or granular form, which was not convenient for common medical treatment operations such as pressing, packing and bandaging when used, and lacked ease of operation. In recent years, loading it on a flexible gauze-like base material to make a composite hemostatic material has become the main improvement direction of such materials. For example, the American Z-Medica company loaded kaolin on a non-woven base material by coating, so that the material can be easily pressed, packed and bandaged. The product is called combat gauze. Once launched, it quickly became the first-line hemostatic material of the US military and is still in use today. However, due to the use of a water-soluble adhesive, most of the kaolin particles will fall off the non-woven base material as soon as the kaolin gauze comes into contact with water or blood. Although the kaolin powder particles falling off the gauze during use hardly affect the effectiveness of hemostasis, after the hemostasis is completed, the adhesive residue of the kaolin particles on the wound surface makes debridement difficult. In addition, the detached kaolin particles may have the safety risk of entering the blood vessels to form thrombi, which has partially questioned its safety. A product that used montmorillonite as an active hemostatic material was forced to be withdrawn from the market because it was discovered that montmorillonite particles entered the blood vessels and caused blood clots during use.
[0005] Since 2019, Zhejiang University has reported a flexible zeolite gauze product with strong bonding between inorganic hemostatic materials and flexible substrate materials (ZL201810625864.0). This product grows zeolite crystal particles directly on the absorbent cotton gauze substrate by in-situ growth. The two are connected by strong covalent bonds, and the zeolite and absorbent cotton gauze are firmly integrated without the use of a binder. The product meets the requirements of high efficiency, ease of operation, portability and biosafety. However, in the actual production and use of the product, the zeolite powder still falls off. When the zeolite gauze is shaken in water, a powder shedding rate of about 1% can be detected. When the zeolite gauze is slapped and rubbed in a dry state, powder shedding to form dust can also be detected. Although there is no evidence that these shed powders may enter the blood vessels and form thrombi during use, under the high standards for medical device products, they are currently only allowed to be used on the body surface and cannot be used for hemostatic operations in the cavity. At the same time, during the production and processing process of cleaning, slitting, folding, and packaging, zeolite gauze powder falls off to form air dust, which has a certain impact on the equipment and workshop working environment.
[0006] The inventor team proposed Chinese patent ZL202310020148.0 earlier, which announced a technology for directly applying powder particles of inorganic mineral hemostatic materials such as zeolite, kaolin, montmorillonite, and halloysite to the surface of a flexible gauze base material using an aqueous colloidal emulsion (latex) of a rubber-based polymer as a binder to prepare a composite hemostatic material. The hemostatic effectiveness of the hemostatic gauze products obtained by this technical solution is slightly lower than that of the flexible zeolite gauze products obtained by in situ growth, but the powder shedding rate can be significantly reduced to below 0.2%. The higher the amount of rubber binder used, the lower the powder shedding rate. The amount of rubber used usually needs to be one-sixth to one-quarter of the weight of the inorganic powder to achieve a good bonding effect. In other words, when the inorganic hemostatic active components such as zeolite account for 15-20% of the product, the weight of the rubber binder in the entire product is generally 3.0-5.0% to play a good bonding role. Reducing the amount of binder used will rapidly increase the powder shedding rate. In this technical solution, the rubber material obtained after latex drying is used as a binder so that the final product maintains the flexible state of gauze. However, later studies have found that since the chemical stability of the rubber component is significantly lower than that of gauze base materials such as inorganic mineral hemostatic materials and absorbent cotton, the use of a large amount of rubber binders reduces the storage stability and biosafety of the product. We found that when the product with a high content of rubber binder is stored at 60°C and tested for aging resistance, the product is prone to yellowing, the shedding rate of the rubber rises rapidly after aging to a certain period, and the cytotoxicity in the biosafety test increases. In theory, after adding an antioxidant to the rubber, the anti-aging performance of the rubber can be improved and the storage shelf life of the product can be extended. However, since most antioxidants have certain toxicity, the cytotoxicity of the product with the antioxidant is significantly enhanced. Since hemostatic products need to contact with blood and organs, if antioxidants are added to the product, the possibility of dissolution of the antioxidant will greatly increase the difficulty and cost of product safety risk assessment. In summary, although the prior art can achieve the preparation of zeolite hemostatic gauze with strong coagulation ability (high efficiency), flexible gauze morphology (easy operation), and ultra-low powder shedding rate (<0.2%) (safety) by coating inorganic hemostatic materials onto flexible gauze base materials using rubber adhesives, the use of a large amount of rubber adhesives reduces the storage stability and biosafety of the product and shortens the shelf life of the product. At the same time, the in vitro coagulation time of the product is slightly longer than that of the in situ grown flexible zeolite gauze product, which is also a disadvantage.
[0007] The inventor team also proposed Chinese patent ZL202310019643.X earlier, which disclosed a method of coating the surface of a flexible zeolite gauze prepared in advance by in-situ growth technology with a rubber polymer colloidal emulsion, and forming a discontinuous self-adhesive coating (or pressure-sensitive adhesive coating) on the surface of the zeolite gauze material after drying to reduce the powder shedding rate of the zeolite gauze. In this scheme, since the zeolite and the gauze substrate are composited by in-situ growth, no adhesive is required. The self-adhesive coating is only used to reduce the possibility of powder shedding, so the dosage is relatively low, only 0.2%-2.0%. Under the condition of the same zeolite content, the amount of rubber adhesive used in this technical scheme is approximately 10-20% of the amount of rubber adhesive used in ZL202310020148.0, which greatly reduces the content of rubber components with poor chemical stability. However, since the self-adhesive coating formed by the adhesive will partially cover the surface of the zeolite, this scheme will reduce the procoagulant ability of the material. The data in the patent show that when the coating amount of the binder is less than 0.5%, the in vitro coagulation time is extended by an average of 10-20 seconds compared with the uncoated sample; when the coating amount is 0.8%, the in vitro coagulation time is extended by an average of 16-25 seconds compared with the uncoated sample; when the coating amount is further increased to 1.0%-3.0%, the in vitro coagulation time is extended by 30-40 seconds compared with the uncoated sample; when the coating amount of the binder reaches 4%, the in vitro coagulation time is extended by more than 50 seconds compared with the uncoated sample, which is equivalent to extending the in vitro coagulation time by nearly 40%. In other words, this technical solution can reduce the powder shedding rate of the material and improve the safety of the product, but it will sacrifice the most important hemostatic effectiveness indicator of the material. In practical applications, the faster the hemostasis speed and the less bleeding, the greater the chance of saving lives.
[0008] Therefore, how to further improve the hemostatic performance of hemostatic materials, reduce the shedding rate as much as possible, ensure the flexibility of the product, and ensure the weather resistance and storage stability of the product is a technical problem that needs to be solved urgently in this field. Summary of the invention
[0009] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a zeolite-kaolin composite hemostatic gauze and a preparation method thereof.
[0010] The present invention is achieved in that:
[0011] In a first aspect, the present invention provides a composite hemostatic gauze, comprising a flexible zeolite gauze and a kaolin-adhesive mixed coating;
[0012] The flexible zeolite gauze comprises a flexible gauze base layer and zeolite. The zeolite is one of the hemostatic active materials and is directly nucleated and grown on the flexible gauze base by an in-situ growth technique. The zeolite and the flexible gauze base are directly connected by a covalent bond and are independent of a binder.
[0013] The kaolin-self-adhesive mixed coating is made of the kaolin or kaolin-like mineral as the second hemostatic active material, which is evenly mixed with the adhesive, coated on the flexible zeolite gauze and then dried; the kaolin-self-adhesive mixed coating covers the flexible gauze base and part of the zeolite surface, but does not exist between the zeolite and the flexible gauze base.
[0014] Preferably, the weight ratio of the zeolite to kaolin or kaolin-like mineral is 1.5:1-10:1.
[0015] Preferably, the weight ratio of the adhesive to the composite hemostatic gauze is 0.4%-1.2%.
[0016] Preferably, the binder is an aqueous polymer latex diluent, which includes polymer latex particles dispersed in water; the glass transition temperature of the polymer latex particles is Tg≤25°C, preferably Tg≤0°C, and more preferably Tg≤-15°C; the diameter of the polymer latex particles is 50-500 nanometers, preferably 100-300 nanometers.
[0017] Preferably, the polymer latex particles include one or more of chloroprene rubber, styrene-butadiene rubber, carboxylated styrene-butadiene rubber, polyurethane, pure acrylic rubber, styrene-acrylic rubber, polyacrylate rubber, polytetrafluoroethylene, and oxidized polyethylene; the diameter of the latex particles is between 50-500 nanometers.
[0018] In a second aspect, the present invention provides a method for preparing a zeolite-kaolin composite hemostatic gauze, which specifically comprises the following steps:
[0019] Step 1: preparing a flexible zeolite gauze by an in-situ synthesis method; wherein the flexible zeolite gauze is formed by directly connecting the zeolite and the flexible gauze substrate via a covalent bond, and has nothing to do with the self-adhesive coating;
[0020] Step 2: Prepare a mixed slurry of kaolin or kaolin-like minerals and a binder:
[0021] Step 3: evenly coating the mixed slurry obtained in step 2 on the flexible zeolite gauze;
[0022] Step 4: drying the zeolite gauze coated with the mixed slurry at 70-120° C. to obtain a finished zeolite kaolin composite hemostatic gauze.
[0023] The zeolite in the flexible zeolite gauze in step 1 can be at least one of zeolite crystal materials such as P-type zeolite, A-type zeolite, X-type zeolite, Y zeolite and CHA chabazite, which can be loaded onto the flexible gauze substrate by in-situ synthesis.
[0024] Preferably, the weight loading of zeolite in the flexible zeolite gauze material is 5%-30%, preferably 12%-22%.
[0025] Preferably, the cations of the zeolite contain at least one of calcium ions, silver ions, zinc ions and copper ions, wherein the molar ratio of the calcium ions is 5-99%.
[0026] Preferably, the flexible gauze substrate can be various materials in the form of flexible cloth, including cotton cloth, absorbent cotton gauze, absorbent cotton non-woven fabric, polyvinyl alcohol gauze, polyurethane non-woven fabric, and cloth blended with multiple fibers.
[0027] Step 2 specifically comprises diluting the binder with water to form a binder dilution liquid having a solid content of 0.20wt%-0.80wt%; adding kaolin or kaolin-like mineral powder to the binder dilution liquid, adjusting the pH to between 7.0-10.0, and vigorously stirring to obtain a stably dispersed mixed slurry;
[0028] Preferably, a suspending agent can be added to the mixed slurry of kaolin and binder to increase the stability of the slurry. The suspending agent is xanthan gum, locust bean gum, konjac gum, carrageenan, alginic acid, agar, and a composite mixture thereof. The mass concentration of the suspending agent in the mixed slurry is 0.02%-0.08%.
[0029] Preferably, the binder is an aqueous polymer latex diluent, which is composed of polymer latex particles and water as a dispersant. The polymer latex particles are negatively charged or non-ionic, preferably negatively charged.
[0030] Preferably, the weight content of kaolin or kaolin-like minerals in the slurry mixture is 0.50%-5.0%.
[0031] Preferably, the kaolin-like mineral is halloysite or halloysite.
[0032] The weight ratio of the mixed slurry to the zeolite gauze in step 3 is 1:1-4:1.
[0033] In a third aspect, the present invention provides a hemostatic product comprising kaolin or kaolin-like minerals, and zeolite.
[0034] Preferably, the weight ratio of the zeolite to kaolin or kaolin-like mineral is between 1.5:1-10:1, more preferably between 85:15-75:25.
[0035] The beneficial effects of the present invention are:
[0036] The present invention introduces kaolin or kaolin-like minerals into the self-adhesive coating, so that the kaolin or kaolin-like minerals and polymer latex particles have extremely obvious synergistic effects on the surface of the flexible gauze base and part of the zeolite surface. This combination not only greatly improves the hemostatic efficiency of the zeolite gauze, and the in vitro coagulation time is significantly lower than that of the flexible zeolite gauze before the mixed coating is applied, but also significantly reduces the powder shedding rate (significantly reduced to less than 0.2%). In addition, because the technical solution reduces the use of rubber polymer colloidal emulsion, the safety and stability of the material are enhanced, and the shelf life of the product is extended.
[0037] The present invention achieves the improvement of hemostatic performance and aging resistance while maintaining the flexibility of gauze by precisely controlling the weight ratio of zeolite to kaolin or kaolin-like minerals (1.5:1-10:1) and the proportion of binder (0.4%-1.2%). The introduction of kaolin or kaolin-like minerals in the self-adhesive coating not only enhances the procoagulant effect of zeolite, which can be reduced by up to 30 seconds, significantly improving the hemostatic efficiency, but also forms a synergistic effect with the self-adhesive, which improves the chemical stability of the coating, and is more adaptable to environmental factors such as temperature changes, which is conducive to the long-term storage of the product and extends the shelf life of the product.
[0038] In addition, while improving the hemostatic performance and reducing the shedding rate, the flexibility of the product is also well maintained, with almost no obvious difference from before coating, ensuring the convenience and comfort of use. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The figure shows a comparison of the concentrations of activated FXIIa factor in kaolin, zeolite and zeolite-kaolin complex in human plasma after incubation for 1 minute and 5 minutes.
[0040] Figure 2 This is a comparison of the concentrations of activated FXa factor adsorbed on the surface of kaolin, zeolite and zeolite-kaolin composite after incubation in human plasma for 30 minutes.
[0041] Figure 3 The figure is a comparison of the activity of activated thrombin generated by kaolin, zeolite and zeolite-kaolin in human plasma after incubation for 5 minutes and 30 minutes.
[0042] Figure 4 (a) Figure 4(c) in the figure shows the SEM images of the original zeolite gauze (ZG) at different magnifications.
[0043] Figure 4 (b) Figure 4 (d) in the figure shows SEM images of KZG gauze coated with kaolin-self-adhesive mixed coating at different magnifications.
[0044] Figure 5 shows the pressing of ordinary medical absorbent cotton gauze, combat gauze, zeolite gauze and zeolite-kaolin hemostatic gauze on the wound of the rabbit femoral artery bleeding model and the blood clot residue in the wound after the hemostatic material is removed after the hemostatic material is removed. DETAILED DESCRIPTION
[0045] As mentioned above, in view of the shortcomings of the prior art, the inventors of this case proposed the technical solution of the present invention after long-term research and extensive practice. The inventors found that although zeolite, kaolin and some kaolin-like minerals have obvious procoagulant effects as inorganic materials, their working principles are different. When zeolite and kaolin / kaolin-like minerals are mixed and used, there is an extremely obvious synergistic effect. For example, the thrombin activity generated in the coagulation reaction initiated by kaolin is 1.7 U, the thrombin activity generated in the coagulation reaction initiated by zeolite is 3.3 U, and the thrombin activity generated by the mixed hemostatic agent of zeolite and kaolin is 11.3 U, which are 6.6 times that of kaolin and 3.4 times that of zeolite, respectively. Such a significant difference is a completely unexpected result. When the in vitro coagulation time is tested using plasma, the in vitro coagulation time of the mixed sample of zeolite and kaolin is 24 seconds less than the in vitro coagulation time of pure zeolite, and 19 seconds less than the in vitro coagulation time of pure kaolin. When whole blood was used for thromboelastography testing, the clotting time R value of the zeolite-kaolin mixture test was reduced from 3.2 minutes for zeolite to 2.2 minutes. In other words, when zeolite and kaolin are mixed in a certain proportion, a special synergistic effect can be produced, and a significantly higher procoagulant activity is obtained than that of pure zeolite or pure kaolin. However, no obvious synergistic effect was found when zeolite was mixed with other inorganic mineral hemostatic agents, such as mesoporous silica, bioglass, metal oxide powder, or different types of zeolites.
[0046] According to the above latest findings, the present invention provides a new technical route, by coating the surface of the in-situ synthesized zeolite hemostatic gauze with a mixed coating of self-adhesive adhesive and kaolin / kaolin-like minerals, so that the final product contains both zeolite and kaolin / kaolin-like minerals, improves the ability to promote blood coagulation, and contains a small amount of self-adhesive adhesive at the same time. The role of the self-adhesive includes bonding kaolin / kaolin-like minerals to the zeolite gauze and reducing the shedding rate of the zeolite gauze powder. Compared with the technical solution of ZL202310019643.X, due to the addition of kaolin / kaolin-like minerals, this technical route not only does not prolong the coagulation time after applying the self-adhesive coating, but significantly shortens the coagulation time, improves the hemostatic effectiveness of the product, and at the same time, the self-adhesive coating still significantly reduces the shedding rate, and the flexibility of the product is not significantly affected. Compared with the technical solution of ZL202310020148.0, this technical route greatly reduces the amount of binder used, and the binder content in the product is reduced from 3.0-5.0% to 0.4-1.2%, which increases the storage stability and biosafety of the material. In particular, it is found that the addition of kaolin also greatly improves the chemical stability of the self-adhesive coating, and the high temperature resistance and aging resistance are significantly improved. Compared with the existing technical route, the product provided by the present invention is closer to the requirements of an ideal emergency hemostatic material in all indicators.
[0047] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0048] The present invention provides a composite hemostatic gauze, comprising a flexible zeolite gauze and a kaolin-adhesive mixed coating;
[0049] The flexible zeolite gauze comprises a flexible gauze base layer and zeolite. The zeolite is one of the hemostatic active materials and is directly nucleated and grown on the flexible gauze base by an in-situ growth technique. The zeolite and the flexible gauze base are directly connected by a covalent bond and are independent of a binder.
[0050] The kaolin-self-adhesive mixed coating is made of the kaolin / kaolin-like mineral as the second hemostatic active material, which is evenly mixed with the adhesive, coated on the flexible zeolite gauze and then dried; the kaolin-self-adhesive mixed coating covers the flexible gauze base and part of the zeolite surface, but does not exist between the zeolite and the flexible gauze base.
[0051] The weight ratio of the zeolite to kaolin / kaolinoid mineral is 1.5:1-10:1. The weight ratio of the binder to the composite hemostatic gauze is 0.4%-1.2%.
[0052] The binder adopts aqueous polymer latex diluent, and the aqueous polymer latex diluent comprises polymer latex particles dispersed in water; the glass transition temperature Tg of the polymer latex particles is less than or equal to 25°C; and the diameter of the polymer latex particles is between 50-500 nanometers.
[0053] The present invention also provides a method for preparing the above-mentioned zeolite-kaolin composite hemostatic gauze, which specifically comprises the following steps:
[0054] Step 1: preparing a flexible zeolite gauze by an in-situ synthesis method; wherein the flexible zeolite gauze is formed by directly connecting the zeolite and the flexible gauze substrate via a covalent bond, and has nothing to do with the self-adhesive coating;
[0055] Step 2: Prepare a mixed slurry of kaolin / kaolin-like minerals and a binder:
[0056] The binder is diluted with water to form a binder dilution liquid with a solid content of 0.20wt%-0.80wt%; kaolin / kaolin-like mineral powder is added to the binder dilution liquid, the pH is adjusted to between 7.0-10.0, and the mixture is stirred vigorously to obtain a stably dispersed mixed slurry; the weight content of kaolin / kaolin-like mineral in the mixed slurry is 0.50%-5.0%;
[0057] Step 3: evenly apply the mixed slurry of kaolin / kaolin-like mineral and binder obtained in step 2 on the flexible zeolite gauze; the weight ratio of the mixed slurry to the zeolite gauze is 1:1-4:1;
[0058] Step 4: drying the zeolite gauze coated with the mixed slurry at 70-120° C. to obtain a finished zeolite-kaolin composite hemostatic gauze.
[0059] The zeolite in the flexible zeolite gauze in step 1 can be at least one of zeolite crystal materials such as P-type zeolite, A-type zeolite, X-type zeolite, Y-type zeolite and CHA chabazite, which can be loaded onto the flexible gauze substrate by an in-situ synthesis method. The existing technology can already realize the in-situ growth synthesis of the above zeolites.
[0060] Preferably, the weight loading of zeolite in the flexible zeolite gauze material is 5%-30%. Too low loading affects the hemostatic effect, and the flexibility of the material with a loading exceeding 30% is significantly reduced, affecting use. Therefore, 5%-30% is selected, and the interval of 12%-22% is particularly further preferred. In this interval, the hemostatic effect is stable and the flexibility is kept better.
[0061] A large number of documents prove that the presence of some calcium ions in zeolite is conducive to its procoagulant function. Therefore, the molar ratio of calcium ions in the metal cations in the zeolite is 5-99%, which can improve the coagulation function of the hemostatic gauze. In addition, a large number of documents prove that when the cations of the zeolite contain a small amount of silver ions, zinc ions, or copper ions and their mixtures, the material can be given antibacterial and antiviral properties. In the present application, the zeolite can also be treated with common cation exchange to allow the zeolite to contain a small amount of silver ions, copper ions or zinc ions and their mixtures, so that the produced zeolite hemostatic gauze material has both hemostatic and antibacterial and antiviral effects.
[0062] The flexible gauze substrate in the flexible zeolite gauze can be various materials in the form of flexible cloth, including cotton cloth, absorbent cotton gauze, absorbent cotton non-woven fabric, polyvinyl alcohol gauze, polyurethane non-woven fabric, and cloth blended with multiple fibers.
[0063] In the mixed slurry of kaolin / kaolinoid mineral and binder described in step 2, a suspending agent can also be added to increase the stability of the slurry. The suspending agent adopts xanthan gum, locust bean gum, konjac gum, carrageenan, alginic acid, agar and its composite mixture. Kaolin / kaolinoid minerals have extremely strong negative charges under neutral and alkaline conditions, and the surface charge density is higher than that of most other inorganic powders, so the stability of kaolin / kaolinoid minerals directly dispersed in water is better. Therefore, when the material tank of the coating equipment is equipped with devices such as bubbling and stirring, a basically stable slurry can be obtained without adding a suspending agent. However, if the coating equipment material tank does not have the above-mentioned device, a suspending agent and a thickener can also be added to the mixed slurry to improve the slurry stability and ensure the consistency of the product coating. The mass concentration of the suspending agent in the mixed slurry is controlled between 0.02%-0.08%. Too low a concentration does not have the effect of suspension stability, and too high a concentration reduces the chemical stability of the product and also affects the softness of the product.
[0064] The binder adopts an aqueous polymer latex diluent, which is composed of polymer latex particles and water as a dispersant. In order to ensure the stability of the colloidal particle dispersion, the formula is generally intentionally controlled in the production process so that these colloid surfaces generally have positive and negative charges or non-ionic surfactant components. If only the self-adhesive adhesive coating is applied, the polymer latex particles in the latex can be positively charged particles, negatively charged particles, or particles with non-ionic surfactant components. However, since kaolin / kaolinoid minerals are materials with strong negative charges on the surface, the polymer latex particles must be selected as negatively charged and non-ionic. The mixing of positively charged polymer latex particles and kaolin / kaolinoid minerals will form flocculation precipitation due to the charge attraction. Therefore, the preferred negatively charged latex in this application is used as the precursor of the self-adhesive component, and the mixed dispersion system is more stable.
[0065] The kaolin-like mineral is halloysite or kaolinite, which has a crystal structure and composition similar to kaolin. It is also a dioctahedral aluminosilicate with a 1:1 type structural unit layer, but there is interlayer water between the structural unit layers, so it is also called kaolinite. It loses most of its interlayer water at 50-90°C and becomes metamorphic halloysite, which is a polymorph of kaolinite. The crystals of kaolin are planar crystal structures, while halloysite is a tubular structure wound by planar crystals. The physical and chemical properties of the two are very similar, so halloysite is sometimes also called tubular kaolin and kaolinite. We found that there is also a synergistic effect between halloysite and zeolite. Therefore, the kaolin described in this application includes kaolin in the traditional sense, and also includes kaolin-like minerals such as halloysite and kaolinite.
[0066] The rubber in the polymer latex refers to the self-adhesive coating formed after the latex dries, which is in a rubber state at room temperature. The glass transition temperature (T g ) is usually below zero. When the ambient temperature is significantly higher than the glass transition temperature of this type of polymer material, the material has good flexibility and elasticity. The soft feel of the hemostatic material after coating can be maintained.
[0067] The polymer latex particles include one or a combination of chloroprene rubber, styrene-butadiene rubber, carboxylated styrene-butadiene rubber, polyurethane, pure acrylic rubber, styrene-acrylic rubber, polyacrylate rubber, polytetrafluoroethylene, and oxidized polyethylene; the diameter of the latex particles is between 50 and 500 nanometers.
[0068] Each latex listed above is just a general term for a large category of latex, and does not refer to a chemical with a completely determined composition. For example, the monomers of polyacrylate latex can be methyl acrylate, propyl acrylate, butyl acrylate and mixtures thereof, and even other types of monomers such as acrylic acid monomers and acrylonitrile monomers can be added to achieve the regulation of glass transition temperature, surface charge, cohesion and other indicators; the glass transition temperature of the product can be adjusted according to the selection and proportion of monomers. Another example is carboxylated styrene butadiene latex, whose main monomers include styrene, butadiene and acrylic acid. Changing the ratio of styrene and butadiene can adjust the glass transition temperature of the material; this regulation technology is a prior art and is a technical means known to those skilled in the art.
[0069] The coating in step three may refer to any technical method for uniformly coating the slurry onto the zeolite gauze substrate, including dipping, roller coating, extrusion coating, spraying, scraping, brushing, shower coating, etc.
[0070] The concentration of the slurry in step 2 and the coating ratio in step 3 determine the content of kaolin / kaolinoid minerals and rubber binder components contained in the final product. For example, if the goal is to apply 4% of kaolin / kaolinoid minerals to zeolite gauze, the content of kaolin / kaolinoid minerals in the slurry in step 2 can be matched to 2%, and the coating ratio in step 3 is controlled to apply 2 grams of slurry per gram of zeolite gauze. Or the content of kaolin / kaolinoid minerals in the slurry in step 2 is matched to 2.5%, and then the coating ratio in step 3 is controlled to apply 1.6 grams of slurry per gram of zeolite gauze. The coating ratio needs to be determined according to the liquid absorption capacity of the base material and the equipment conditions. If the coating ratio is too low, the slurry may not be spread to all positions, and some places are dry and some places are wet, affecting the coating uniformity. If the coating ratio is too high, exceeding the saturated liquid absorption rate of the base material, it will cause uncontrolled loss of slurry, difficult equipment handling, and high energy consumption required for drying. Therefore, it is necessary to determine the coating ratio based on the liquid absorption characteristics of the base material and the parameters of the coating equipment, and then calculate the slurry concentration based on the target coating amount requirements.
[0071] It should be noted that there are many methods for testing coagulation time, such as the in vitro coagulation time obtained by adding hemostatic materials to bovine plasma, the in vitro coagulation time obtained by adding hemostatic materials to human whole blood, and the coagulation factor reaction time (R value) obtained by adding hemostatic materials to human whole blood on a thromboelastometry. The above values can all be used to characterize the effect of hemostatic materials. In the data obtained by the same test method, the shorter the coagulation time, the better the procoagulant effect of the material. However, due to different test methods, the results of different test methods for different materials cannot be directly compared. For example, the in vitro coagulation time obtained by testing bovine plasma of zeolite X and the in vitro coagulation time obtained by testing human whole blood of zeolite Y cannot be used to directly compare the procoagulant effects of zeolite X and zeolite Y. In addition, even if the same method is used, the activity levels of coagulation factors contained in each batch of plasma and whole blood are not completely consistent, so the test results of different batches of plasma or whole blood for the same material will also fluctuate. The data reported in the examples of this application are all derived from the same batch of plasma or whole blood, tested under the same conditions, and the values can be directly used to compare the differences in the procoagulant effects between the materials. However, the data between different examples may not be directly used for comparison across examples because different batches of plasma are used. For example, the in vitro coagulation time of pure kaolin / kaolinoid minerals is slightly different in different examples because of the errors in the test itself and the different effects of the plasma batches used.
[0072] The technical solution of the present invention will be clearly and completely described below in conjunction with the best embodiment. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0073] Example 1
[0074] Commercial A-type zeolite, X-type zeolite, Y-type zeolite and P-type zeolite were purchased, and each type of zeolite was immersed in a 2 mol / L calcium chloride aqueous solution at a weight ratio of 1:25 for calcium ion exchange. The exchange was repeated three times, and a freshly prepared calcium chloride aqueous solution was used for exchange each time. The sodium ions in the zeolite were exchanged for calcium ions. Purchasing kaolin that had been washed and purified, with a purity greater than 96%, chitosan powder, mesoporous silica MCF material, and ochre powder. Bovine plasma was used to test the in vitro coagulation time of various zeolites that had been exchanged with calcium, the in vitro coagulation time of pure kaolin, and the in vitro coagulation time of mixtures of different zeolites and kaolin in different proportions, as well as the in vitro coagulation time of mixtures of other materials with procoagulant ability. In the in vitro coagulation time test experiment of each material, the total weight of the procoagulant material was fixed at 15 mg, the volume of plasma was fixed at 1 ml, and the plasma temperature was constantly controlled at 37°C. The test results are shown in Table 1.
[0075] Table 1
[0076]
[0077] From the test results, when zeolite A, zeolite X, zeolite Y and zeolite P are mixed with kaolin, their in vitro clotting time (serial number 6-9) is shorter than the in vitro clotting time of the corresponding pure zeolite (serial number 2-5) or pure kaolin (serial number 1). When different zeolites are mixed (serial number 10-13), the in vitro clotting time is generally between the in vitro clotting times of two different zeolites. This shows that there is a synergistic effect when zeolite and kaolin are mixed, but there is no obvious synergistic effect when zeolite and zeolite are mixed. There is no obvious synergistic effect between zeolite and other procoagulant active substances such as mesoporous silica and chitosan (serial number 14-16), and the in vitro clotting time is longer than that of pure zeolite itself. When kaolin is mixed with chitosan powder, mesoporous silica and ochre, there is no synergistic effect (serial number 17-19), and the in vitro clotting time of the mixture is longer than that of pure kaolin. The above experimental results show that not any two materials with procoagulant ability can achieve the effect of 1+1 greater than 2 after mixing. Zeolite and kaolin have a special synergistic effect, which makes the mixture have a higher procoagulant ability than either component alone.
[0078] Example 2: Testing the in vitro coagulation time of kaolin powder, Y zeolite after calcium ion exchange, and mixtures of different proportions.
[0079] In the in vitro coagulation time test experiment of each material, the total weight of the inorganic material was fixed at 15 mg, the volume of porcine plasma was fixed at 1 ml, and the plasma temperature was constantly controlled at 37°C. We first conducted the first round of ratio optimization experiments within a large range of the ratio of the two, and then conducted the second round of ratio optimization experiments by further subdividing the test points near the optimal point. The test results are shown in Table 2.
[0080] Table 2
[0081]
[0082] As can be seen from the table above, when the ratio between zeolite and kaolin is 85:15 (5.7:1) to 75:25 (3:1), the in vitro coagulation time of the mixture is the shortest, and the in vitro coagulation time is 102-104 s. It is about 28 seconds shorter than pure zeolite and 22 seconds shorter than pure kaolin. The optimal ratio of kaolin is between 15-25%. When the zeolite-kaolin ratio range is expanded to 90:10 (9:1) to 60:40 (1.5:1), that is, when the kaolin component accounts for 10%-40%, the in vitro coagulation time is less than 110 seconds, which is still significantly more advantageous than pure zeolite or kaolin. Outside the above range, mixing also has the benefit of synergistic effect, but the benefits are not as significant as in the above optimization range. It should be pointed out that since the coagulation cascade reaction is a multi-step complex physiological catalytic process that requires the participation of more than a dozen coagulation factors, the coagulation time cannot be shortened indefinitely. For this type of procoagulant process without the involvement of biological agents, it is very difficult to further improve the in vitro clotting time after it is less than 130 seconds. Therefore, in this test, the reduction of the in vitro clotting time of zeolite from 131 seconds to 102 seconds after adding a small amount of kaolin can be considered an extremely significant improvement. This represents a significant increase in the reaction rate of the reaction steps in the coagulation cascade that are related to zeolite and kaolin.
[0083] Example 3
[0084] Different types of zeolites were selected and mixed with halloysite powder and halloysite in different proportions, and then the in vitro coagulation time was tested. The test method was the same as in Example 1. The results obtained are described as follows: When Y zeolite and halloysite were mixed in a ratio of 4:1, the in vitro coagulation time was 114 seconds, which was less than 129 seconds of pure Y zeolite itself and 127 seconds of pure halloysite. When P zeolite and halloysite were mixed in a ratio of 3:1, the in vitro coagulation time was 118 seconds, which was less than 136 seconds of pure P zeolite and 129 seconds of pure halloysite. The above results show that there is also an obvious synergistic effect of promoting coagulation between zeolite and halloysite and halloysite.
[0085] Example 4
[0086] A mixture of calcium Y zeolite and kaolin (KZ) with a weight ratio of 4:1 was selected as the optimized combination, and pure calcium Y zeolite (Z) and pure kaolin (K) were used as control samples to study their ability to activate several specific coagulation factors in the coagulation cascade reaction. The specific process is briefly described as follows:
[0087] (1) 12.5 mg of the sample was mixed with 100 μl of human plasma and 900 μl of pure water, incubated at 37°C for 1 minute and 5 minutes, then the incubation process was terminated and the concentration of activated FXIIa factor in the sample was analyzed by Western blot. The specific results are shown in Figure 1 .
[0088] (2) 250 mg of the sample was mixed with 1 ml of human plasma and incubated at 37°C for 30 minutes. The concentration of activated FXa factor adsorbed on the surface of the material was detected by Western blot. The specific results are shown in Table Figure 2 .
[0089] (3) Mix 50 mg of sample with 200 μl of human plasma and incubate at 37°C. Use the thrombin chromogenic substrate method to detect the activity of thrombin activated in the test system when the incubation time is 5 minutes and 30 minutes. The specific test data results are shown in Figure 3 .
[0090] from Figure 1 It can be seen that after 1 minute, the concentration of activated FXIIa factor obtained by the kaolin sample was higher than that of zeolite, because the surface of kaolin carries a higher concentration of negative charge and has a stronger ability to activate FXII factor. However, after 5 minutes, there was not much difference between the two, and it may have reached the peak, indicating that the activation rate of kaolin is faster than that of zeolite, which is consistent with literature reports. However, surprisingly, the zeolite-kaolin mixed sample (KZ) significantly activated more FXIIa regardless of whether it was 1 minute or 5 minutes. When the incubation time was 5 minutes, the FXIIa value of the KZ sample was 16500 au, which was nearly twice as high as that of pure zeolite (9450 au) and pure kaolin (8090 au). From Figure 2 It can be seen that there is almost no FXa on the surface of kaolin, because kaolin does not participate in the activation process of FX factor, which is consistent with the results reported in the literature. However, the value of activated FXa adsorbed on the surface of KZ sample is 3730 au, which is 6.4 times that of the activated FXa value (578 au) on the surface of pure zeolite sample. Figure 3It can be seen that, whether it is the 5-minute data or the 30-minute data, the activity value of KZ-activated thrombin is 3 times that of the activation result of pure zeolite and about 7 times that of pure kaolin.
[0091] The following results can be obtained from the above data: (1) Consistent with the conclusions reported in the literature, both kaolin and zeolite can participate in the activation of FXII factor, but kaolin is significantly more active in this step. At one minute, pure kaolin activated significantly more FXIIa than zeolite. Zeolite can also participate in the activation of FX factor and increase the activity of thrombin. This step is the main mechanism of zeolite in promoting blood coagulation. (2) After zeolite and kaolin are mixed, whether in the activation of FXII factor, the activation of FX factor or the activation of thrombin, they show super high activation effect relative to pure zeolite and pure kaolin. The activity produced is several times that of the control sample. It is not a simple addition of the two, but a significant synergistic effect. The existing literature does not suggest that a simple mixture of the two can produce such a huge improvement. (3) The further mechanism of the synergistic effect of kaolin and zeolite disclosed in the present invention has not been studied or reported in any literature.
[0092] Example 5: Distribution incubation test results
[0093] The plasma was incubated with kaolin in advance for different time periods, and then centrifuged to remove the kaolin before adding zeolite to test the in vitro coagulation time and the activity of thrombin activated in the system. The specific results are shown in Table 3.
[0094] Table 3
[0095]
[0096] From the above results, we can see that the coexistence of zeolite and kaolin at the same time and in the same place can make the synergistic effect of the two more efficient. Contact with kaolin first may produce a higher level of FXIIa, but after a long interval, contact with zeolite may not necessarily have a synergistic effect. This may be related to the half-life of various coagulation factors in the blood after activation. The freshly produced coagulation factors need to enter the next coagulation cascade reaction immediately to be effective. This experiment further illustrates the importance of the coexistence of zeolite and kaolin on the same material.
[0097] Example 6
[0098] According to the technology disclosed in ZL202310020148.0, a slurry is prepared, and zeolite is coated on an absorbent gauze base to obtain a zeolite gauze hemostatic material. The slurry contains 10% zeolite, 1.8% styrene-butadiene latex, 0.06% xanthan gum and 0.04% konjac gum. The coating ratio of the slurry and the absorbent gauze is 2.1 grams of slurry per gram of absorbent gauze. After drying at 100 degrees, the zeolite hemostatic gauze material is obtained. The actual test in the hemostatic gauze contains about 16.8% of roasting ash, which can be regarded as the content of the active component of the zeolite. The content of the rubber binder is calculated to be approximately 3% based on the concentration of the binder in the slurry and the weight ratio of the slurry and the base gauze during coating. The sample number is recorded as S6-A. There is also a flexible zeolite gauze prepared by the in-situ growth method obtained from Hangzhou Feichuang Life Science Co., Ltd., with a zeolite loading of 18.2%, and the sample number is recorded as S6-B. Both of the above materials are cut and folded into 10 grams / bag, sealed in an aluminum foil bag, and then subjected to a temperature-increasing accelerated aging treatment in a 60°C constant temperature box. Some samples are taken out regularly to test various indicators. Among them, the coagulation time is the in vitro coagulation time of the bovine plasma test, the shedding rate is the shedding rate of the inorganic powder in water, and the survival rate is the cell survival rate data detected by the MTT method in the in vitro cytotoxicity test. The specific results are shown in Table 4.
[0099] Table 4
[0100]
[0101] From the above results, the zeolite gauze (S6-B) synthesized by the in situ growth method did not deteriorate significantly in the aging experiment of 132 days: the coagulation time was between 130-140 s, the shedding rate was between 0.65%-0.85%, and the powder shedding rate was high. The cell survival rate was greater than 75%, meeting the requirements of medical device cytotoxicity testing. The above results show that the shelf life of the product at room temperature is greater than three years. This is related to the simple composition of the product. The shelf life of absorbent cotton gauze is longer, and zeolite material, as an inorganic mineral material, hardly undergoes any degradation reaction at room temperature. The product does not contain other components. For the zeolite hemostatic gauze (S6-A) prepared by the coating method using styrene-butadiene rubber as a binder, its in vitro coagulation time remains between 145-155 s and remains stable. Under the condition of similar zeolite content, the in vitro coagulation time is greater than that of the in situ grown material, which may be related to the partial coverage of the zeolite surface by the binder. During the temperature-accelerated aging experiment, the powder shedding rate of the material increased significantly after 66 days, and after 132 days, its powder shedding rate increased to 0.37%, which is three times that of the original sample (0.13%). In addition, its cell survival rate gradually decreased with the extension of aging time. After 66 days of aging, the cell survival rate was less than 75%, and after 132 days of aging, the cell survival rate decreased to 34%, which has shown certain toxicity. Since the two components of zeolite and cotton wool are relatively stable, we attribute the decrease in shedding rate and the increase in cytotoxicity to the influence of the byproducts formed by the aging of a large number of rubber binder components during long-term storage. From the above results, it can be seen that the shedding rate of the zeolite gauze obtained by the in situ growth method is higher, and the powder shedding rate of the zeolite gauze obtained by the coating method is significantly lower, but the large amount of rubber binder used in the coating method affects the aging resistance of the material, indicating that the rubber content is high and the product stability and aging resistance are poor. During the aging process, the shedding rate and cytotoxicity of the product increase significantly, which affects the storage stability and shelf life setting of the product.
[0102] Example 7
[0103] Preparation of sample S7-A: Step 1: Obtain flexible zeolite hemostatic gauze prepared by in-situ synthesis from Hangzhou Feichuang Life Science Co., Ltd., with a zeolite loading of 18.2wt%. The sample is the same as S6-B in Example 6. Step 2: Prepare slurry (1), which contains 0.40wt% chloroprene rubber latex, and is prepared by diluting a 50wt% latex stock solution with water. Step 3: Evenly apply the slurry to the zeolite hemostatic gauze S6-B, with a coating ratio of 2.2 grams of slurry per gram of gauze. Step 4: Dry the coated sample at 105 degrees to obtain a zeolite gauze coated with a self-adhesive layer. According to the above process calculation, the gauze contains 18.0wt% zeolite, and the weight of the self-adhesive formed by the chloroprene latex accounts for about 0.87wt%. The sample is recorded as S7-A.
[0104] Preparation of sample S7-B: Step 1: A flexible zeolite hemostatic gauze prepared by an in-situ synthesis method was obtained from Hangzhou Feichuang Life Science Co., Ltd. The zeolite loading was 18.2wt%, and the sample was the same as S6-B in Example 6. Step 2: Prepare a coating slurry (2), the slurry contains 2.0wt% kaolin and 0.40wt% chloroprene rubber latex, and the pH value of the slurry is adjusted to 9.5 with a 0.1M NaOH aqueous solution. Step 3: The above slurry is evenly coated on the zeolite hemostatic gauze S6-B, and the coating ratio is 2.2 grams of slurry per gram of gauze. After drying at 105 degrees, a zeolite-kaolin composite hemostatic gauze is obtained. According to calculations, the gauze contains 16.7wt% zeolite, 4.2wt% kaolin, and 0.84wt% chloroprene rubber. The sample is recorded as S7-B.
[0105] The above two materials were cut and folded into 10 g / bag, sealed in aluminum foil bags, and then subjected to temperature-increasing accelerated aging treatment in a 60°C constant temperature box. Some samples were taken out at regular intervals to test various indicators. The coagulation time is the in vitro coagulation time of bovine plasma test, the shedding rate is the shedding rate of inorganic powder in water, and the survival rate is the cell survival rate data detected by the MTT method in the in vitro cytotoxicity test. The specific results are shown in Table 5.
[0106] Table 5
[0107]
[0108] From the above results, after about 0.87% of the adhesive was coated on the in situ grown flexible zeolite gauze (S6-B), the coagulation time of the material decreased from 130-140 s to 152-163 s, and the hemostasis efficiency decreased significantly. This can be explained by the fact that the adhesive coating covered part of the zeolite surface, affecting its procoagulant effect. This result is consistent with the data published in ZL202310019643.X. However, after the adhesive was applied, the shedding rate dropped significantly to below 0.2%. At the same time, when the aging time was less than 99 days, the cell survival rate was still greater than 75%, and the shelf life of the product met the requirement of three years. However, from the results of 132 days, further aging of the rubber will still further increase the powder shedding rate of the material to more than 0.2%. At the same time, the cell survival rate in the cytotoxicity test began to be lower than 75%, which no longer met the requirements of dressing medical devices. When the in-situ grown flexible zeolite gauze (S6-B) was coated with about 0.84% chloroprene rubber coating and mixed with 4.2% kaolin, the in vitro coagulation time of the material was reduced from 130-140 s of the original zeolite gauze (S6-B) to 110-118 s. Compared with the S7-A sample coated with only adhesive, the in vitro coagulation time was reduced by 40-50 seconds, which was an extremely obvious improvement. This shows that due to the synergistic effect between the two, the addition of kaolin greatly improved the hemostatic efficiency of zeolite hemostatic gauze. At the same time, within the 132-day aging experiment, the powder shedding rate was always less than 0.2%, and the cell survival rate of the cytotoxicity test was always greater than 75%. Its anti-aging performance is better than that when only chloroprene adhesive is coated. This shows that kaolin in this composite material not only improves the procoagulant performance of the material due to the special procoagulant synergistic effect between zeolite and kaolin, but also increases the chemical stability of the rubber coating, thereby improving the overall thermal oxidation aging resistance of the material. According to literature research, the addition of kaolin may reduce the damage to rubber caused by free radicals formed by various environmental stimuli (light, heat, chemical factors), or the addition of kaolin may slow down the diffusion of active oxygen in the rubber coating. The specific reason is unclear. However, from the actual effect, the addition of kaolin not only improves the product's ability to promote blood coagulation, but also enhances the chemical stability of the self-adhesive coating, improves the product's aging resistance, and extends the product's shelf life.
[0109] Example 8
[0110] A composite hemostatic gauze material includes a flexible zeolite gauze and a kaolin-self-adhesive mixed coating, wherein the flexible zeolite gauze is composed of a flexible gauze base layer and zeolite. Zeolite is directly formed on the surface of the flexible gauze base layer by in-situ growth. For specific preparation technology, please refer to patent documents (CN201810625854.7, CN201810625864.0, CN202010803355.X). The self-adhesive component is evenly mixed with the kaolin component, and the mixed coating formed by the self-adhesive and kaolin does not exist between the zeolite and the gauze base layer. The weight ratio of zeolite to kaolin is between 1.5:1-10:1. The proportion of self-adhesive is between 0.4wt%-1.2wt%. The self-adhesive adhesive is obtained by coating and drying a water-based rubber polymer latex dilution liquid, wherein the polymer latex dilution liquid is composed of polymer latex particles dispersed in water and a dispersion medium of water; the glass transition temperature Tg of the polymer latex particles is ≤25°C; the diameter of the polymer latex particles is between 50-500 nanometers. The content of zeolite hemostatic material in zeolite gauze is 5-30wt%, preferably, the content of zeolite hemostatic material in zeolite gauze is 12-22wt%. The zeolite hemostatic material is zeolite, and the crystal form of the zeolite is one or more combinations of A-type zeolite, P-type zeolite, X-type zeolite, Y-type zeolite and chabazite. The molar ratio of calcium ions in metal cations in zeolite is 5-99%, preferably 30-95%.
[0111] The self-adhesive label is obtained by coating and drying a water-based rubber polymer colloidal emulsion dilution liquid, wherein the water-based rubber polymer colloidal emulsion dilution liquid is composed of latex particles dispersed in water and a water solvent.
[0112] The glass transition temperature Tg of the polymer latex particles is ≤25°C.
[0113] Preferably, the polymer latex particles have a glass transition temperature Tg≤0°C.
[0114] Preferably, the polymer latex particles have a glass transition temperature Tg ≤ -15°C.
[0115] The weight of the adhesive is 0.4-1.2 wt% of the total weight of the composite hemostatic gauze material;
[0116] The diameter of the polymer latex particles is between 50 and 500 nanometers, preferably between 100 and 300 nanometers.
[0117] The average bending length of the zeolite hemostatic gauze material is less than 3 cm. The shedding rate of the zeolite hemostatic material in the zeolite hemostatic gauze material in water is less than 0.2%, and it has ultra-low zeolite shedding rate, good flexibility and excellent hemostatic performance.
[0118] The preparation method of the composite hemostatic gauze material provided in this embodiment comprises the following steps:
[0119] Step 1, preparation of flexible zeolite gauze:
[0120] Silica sol with a solid content of 30% is used as the silicon source, ultrafine aluminum hydroxide powder is used as the aluminum source, and sodium hydroxide is used as the sodium source. The materials are mixed and stirred in a ratio of Si:Na:Al:H2O of 7:2:9.5:380 as the precursor liquid of zeolite, and the ratio of gauze to zeolite precursor liquid is 1:7. The reaction temperature is 105°C and the reaction time is 72 hours. After the reaction is completed, the material is washed with tap water until the pH value is less than 9. Anhydrous calcium chloride is added at a ratio of 6% of the weight of the zeolite gauze, and it is prepared into an aqueous solution and then soaked and calcium-added. Part of the sodium ions in the zeolite are replaced by calcium ions through ion exchange operation. Finally, flexible zeolite gauze is obtained by washing and drying. The average zeolite loading in the prepared zeolite gauze is 19.62wt%, and the crystal form of the zeolite is P-type zeolite, in which the calcium ion exchange degree is 51%;
[0121] Step 2: Preparation of kaolin-binder mixed slurry:
[0122] The aqueous rubber polymer colloidal emulsion (latex) raw material with a high solid content is added with water to prepare a latex dilution with a solid content of 0.40% as a binder; kaolin is added, and the pH is adjusted to 8.5 with a 0.1 M sodium hydroxide aqueous solution, and stirred vigorously to obtain a kaolin-latex mixed slurry. The weight ratio of kaolin is 2.2wt%. The rubber latex raw material variety is chloroprene latex.
[0123] Step 3, the water mixed slurry in step 2 is evenly coated on the flexible zeolite gauze by dipping, the weight ratio of the mixed slurry to the zeolite gauze is 2.2:1, that is, 2.2 grams of kaolin-binder mixed slurry is coated per gram of gauze;
[0124] Step 4: The flexible zeolite hemostatic gauze coated with the slurry is dried at 105°C to obtain a finished zeolite-kaolin composite hemostatic gauze material. In the finished zeolite-kaolin composite hemostatic gauze, the zeolite content is 18.56wt%, the kaolin content is 4.58wt%, the adhesive content is 0.83wt%, and the weight ratio of zeolite:kaolin is 4.0:1. The sample is recorded as S8-A.
[0125] The same flexible zeolite gauze raw material was selected. Compared with the synthesis conditions of S8-A, only the latex in step 2 was changed to styrene-butadiene latex, the latex concentration was reduced to 0.30wt%, and other parameters remained unchanged. The zeolite content in the obtained sample was 18.60wt%, the kaolin content was 4.59wt%, the adhesive content was 0.63wt%, and the weight ratio of zeolite to kaolin was 4.0:1. This sample was recorded as S8-B.
[0126] The same flexible zeolite gauze raw material was selected. Compared with the synthesis conditions of S8-A, only the kaolin concentration in step 2 was increased to 3.0, and other parameters remained unchanged. The zeolite content in the obtained sample was 18.25wt%, the kaolin content was 6.14wt%, the adhesive content was 0.82wt%, and the weight ratio of zeolite to kaolin was 3.0:1. This sample was recorded as S8-C.
[0127] The same flexible zeolite gauze raw material was selected. Compared with the synthesis conditions of S8-A, only the kaolin concentration in step 2 was reduced to 1.5, and other parameters remained unchanged. The zeolite content in the obtained sample was 18.83wt%, the kaolin content was 3.17wt%, the adhesive content was 0.84wt%, and the weight ratio of zeolite to kaolin was 6.0:1. This sample was recorded as S8-D.
[0128] The same flexible zeolite gauze raw material was selected. Compared with the synthesis conditions of S8-A, only the kaolin concentration in step 2 was reduced to 1.0, and other parameters remained unchanged. The zeolite content in the obtained sample was 19.03wt%, the kaolin content was 2.13wt%, the adhesive content was 0.85wt%, and the weight ratio of zeolite to kaolin was 8.9:1. This sample was recorded as S8-E.
[0129] The information and test data of the obtained samples are listed in the following table:
[0130] Table 6
[0131]
[0132] From the above data, we can see that after the zeolite gauze is coated with the kaolin-self-adhesive mixed coating, the shedding rate is significantly reduced by 5-10 times. The shedding rate of the uncoated zeolite gauze sample is 0.86%, and the shedding rate is reduced to 0.08%-0.16% after coating with the kaolin-self-adhesive mixed coating. When the kaolin content is high, the shedding rate is high, and when the kaolin content is low, the shedding rate is less than 0.1%. After coating with the kaolin-self-adhesive mixed coating, the in vitro coagulation time is significantly reduced compared to the 136 seconds of the original zeolite gauze. When the ratio of zeolite kaolin is less than 3:1, the in vitro coagulation time is reduced by 30 seconds to 106 seconds. Judging from the bending length values in both the warp and weft directions, the flexibility of the product is maintained very well, with almost no significant difference from before coating.
[0133] Example 9
[0134] A method for preparing a composite hemostatic gauze material comprises the following steps:
[0135] Step 1, preparation of flexible zeolite gauze:
[0136] Sodium silicate aqueous solution water glass is used as silicon source and sodium source, sodium aluminate is used as aluminum source and sodium source, and sodium hydroxide is used as additional sodium source. The materials are mixed and stirred in a ratio of Si:Na:Al:H2O of 11:2:18:650 as the precursor liquid of zeolite, and the ratio of gauze to zeolite precursor liquid is 1:5. The reaction temperature is 120°C and the reaction time is 36 hours. After the reaction is completed, the material is washed with tap water until the pH value is less than 9. Anhydrous calcium chloride is added according to a ratio of 15% of the weight of the raw material absorbent cotton gauze, and it is prepared into an aqueous solution and then soaked and calcium-added. Part of the sodium ions in the zeolite are replaced by calcium ions through ion exchange operation. Finally, flexible zeolite gauze is obtained by washing and drying. The average zeolite loading in the prepared zeolite gauze is 13.28wt%, and the crystal form of the zeolite is X-type zeolite, in which the calcium ion exchange degree is 87%;
[0137] Step 2, preparation of kaolin-binder mixed slurry: dilute the carboxylated styrene-butadiene rubber latex raw material with a high solid content with water to about 1.0wt%, add a certain amount of kaolin powder, adjust the pH to 7.5 with 0.1M sodium hydroxide, and stir vigorously to obtain a mixed slurry. Then add water to adjust to a specified total weight, so that in the mixed slurry, the latex concentration is 0.4wt% and the kaolin concentration is 2.0wt%.
[0138] Step 3, the kaolin-binder mixed slurry in step 2 is evenly coated on the pre-prepared flexible zeolite gauze by spraying, and the droplets are kept at room temperature for 5 minutes to allow the entire zeolite gauze surface to be soaked, and the spraying weight ratio of the mixed slurry to the zeolite gauze is controlled at 1.5:1;
[0139] Step 4: The zeolite hemostatic gauze coated with the mixed slurry is dried at 85°C to obtain a finished zeolite hemostatic gauze material coating. In the finished zeolite hemostatic gauze, the zeolite content is 12.82wt%, the kaolin content is 2.90wt%, the adhesive content is 0.58wt%, and the weight ratio of zeolite to kaolin is 4.4:1. The sample is recorded as S9-A.
[0140] The same flexible zeolite gauze raw material was selected. Compared with the synthesis conditions of S9-A, only the latex concentration in step 2 was increased to 0.50wt%, the kaolin concentration was increased to 3.0wt%, and other parameters remained unchanged. The zeolite content in the obtained sample was 12.62wt%, the kaolin content was 4.28wt%, the adhesive content was 0.71wt%, and the weight ratio of zeolite to kaolin was 3.0:1. This sample was recorded as S9-B.
[0141] The same flexible zeolite gauze raw material was selected. Compared with the synthesis conditions of S9-A, only the latex concentration in step 2 was increased to 0.60wt%, the kaolin concentration was increased to 4.0wt%, and other parameters remained unchanged. The zeolite content in the obtained sample was 12.42wt%, the kaolin content was 5.61wt%, the adhesive content was 0.84wt%, and the weight ratio of zeolite:kaolin was 2.2:1. This sample was recorded as S9-C.
[0142] The same flexible zeolite gauze raw material was selected. Compared with the synthesis conditions of S9-A, only the latex concentration in step 2 was increased to 0.70wt%, the kaolin concentration was increased to 5.0wt%, and other parameters remained unchanged. The zeolite content in the obtained sample was 12.23wt%, the kaolin content was 6.91wt%, the adhesive content was 0.97wt%, and the weight ratio of zeolite to kaolin was 1.8:1. This sample was recorded as S9-D.
[0143] The same flexible zeolite gauze raw material was selected. Compared with the synthesis conditions of S9-A, only the latex concentration in step 2 was increased to 0.80wt%, the kaolin concentration was increased to 6.0wt%, and other parameters remained unchanged. The zeolite content in the obtained sample was 12.05wt%, the kaolin content was 8.17wt%, the adhesive content was 1.09wt%, and the weight ratio of zeolite to kaolin was 1.5:1. This sample was recorded as S9-E.
[0144] The same flexible zeolite gauze raw material was selected. Compared with the synthesis conditions of S9-A, only the latex concentration in step 2 was increased to 0.50wt%, kaolin was not added, and other parameters remained unchanged. The zeolite content in the obtained sample was 13.18wt%, the kaolin content was zero, and the adhesive content was 0.74wt%. This sample was recorded as S9-F.
[0145] The water shedding rate of the above samples was tested, and the in vitro coagulation time of the above samples was tested using bovine plasma. The results are shown in Table 7.
[0146] Table 7
[0147]
[0148] From the above data, it can be seen that after the original flexible zeolite gauze was coated with kaolin-adhesive mixed coating, the shedding rate was significantly reduced by 5-10 times. The shedding rate of the original flexible zeolite gauze without kaolin-adhesive mixed coating was 0.73%. After adding kaolin-adhesive mixed coating, the shedding rate was significantly reduced to less than 0.2%. At the same time, the in vitro coagulation time was reduced to 109-122 seconds from 152 seconds before coating, which was reduced by 43 seconds at most. While improving the procoagulant ability of zeolite gauze, kaolin-adhesive mixed coating also greatly reduced the powder shedding rate. S9-F is used as a comparative example, and carboxyl styrene-butadiene rubber is coated on the original zeolite gauze, but kaolin component is not added. At this time, the shedding rate of the sample is also greatly reduced to 0.06%, but the in vitro coagulation time is increased by 15 seconds compared with the original zeolite gauze. The extension of the in vitro clotting time caused by the application of the self-adhesive coating can be explained by the fact that the self-adhesive coating covers part of the surface of the zeolite. The huge difference in in vitro clotting time between S9-F and the other five examples (S9-A to S9-E) further verifies the huge benefits of the synergistic effect between zeolite and kaolin.
[0149] Example 10
[0150] S10-A: The zeolite gauze produced by in-situ synthesis technology provided by Hangzhou Feichuang Life Science Co., Ltd. is used as raw material. The zeolite loaded on the zeolite gauze is type A zeolite, the calcium exchange rate of the zeolite is 37%, the gauze matrix is a mesh pattern pure cotton non-woven fabric substrate, and the zeolite loading is 15.64wt%. The latex used in the configured slurry is styrene-acrylic rubber, the kaolin content in the slurry is 2.5wt%, and the latex concentration is 0.40wt%. 0.04wt% xanthan gum and 0.02wt% konjac gum are also added to the slurry as suspending agents to improve the stability of the slurry. The slurry is applied to the zeolite gauze by brushing, and the coating ratio is 1.2:1, that is, 1.2 grams of slurry are applied per gram of gauze. After drying at 95℃, the zeolite-kaolin composite hemostatic gauze is obtained. The gauze contains 15.11wt% zeolite, 0.46wt% adhesive component, and the weight ratio of zeolite to kaolin is 5.21:1. The test results show that after coating, the zeolite shedding rate is reduced from 1.23% of the raw gauze to 0.21% of the composite hemostatic gauze, and the in vitro coagulation time is reduced from 142 seconds of the raw gauze to 121 seconds of the composite hemostatic gauze.
[0151] S10-B: The zeolite hemostatic cloth produced by in-situ synthesis technology provided by Hangzhou Feichuang Life Science Co., Ltd. is used as raw material. The zeolite loaded on the zeolite hemostatic cloth is CHA type zeolite, the calcium exchange rate of the zeolite is 69%, the matrix is a cotton cloth substrate, and the zeolite loading is 8.69wt%. The latex used in the configured slurry is pure propylene rubber, the kaolin content in the slurry is 1.5wt%, and the latex concentration is 0.30wt%. The slurry is coated on the zeolite gauze by dip coating, and the coating ratio is 2.9:1, that is, 2.9 grams of slurry are coated per gram of gauze. After drying at 105℃, the zeolite-kaolin composite hemostatic gauze is obtained. The gauze contains 8.26wt% zeolite, the content of the self-adhesive component is 0.83wt%, and the weight ratio of zeolite to kaolin is 2.0:1. The test results show that after coating, the zeolite shedding rate is reduced from 0.64% of the raw gauze to 0.09% of the composite hemostatic gauze, and the in vitro coagulation time is reduced from 132 seconds of the raw gauze to 108 seconds of the composite hemostatic gauze.
[0152] S10-C: The zeolite gauze produced by in-situ synthesis technology provided by Hangzhou Feichuang Life Science Co., Ltd. is used as raw material. The zeolite loaded on the zeolite gauze is Y-type zeolite, the calcium exchange rate of the zeolite is 89%, the gauze matrix is a mesh pattern pure cotton non-woven fabric substrate, and the zeolite loading is 18.64wt%. The latex used in the configured slurry is polyacrylate, the halloysite content in the slurry is 2.0wt%, the latex concentration is 0.50wt%, and 0.05% xanthan gum is added to the slurry as a suspending agent to improve the stability of the slurry. The slurry is applied to the zeolite gauze by brushing, and the coating ratio is 1.8:1, that is, 1.8 grams of slurry is applied per gram of gauze. After drying at 105℃, the zeolite-halloysite composite hemostatic gauze is obtained. The gauze contains 17.84wt% zeolite, the content of the self-adhesive component is 0.86wt%, and the weight ratio of zeolite-halloysite is 5.18:1. The test results show that after coating, the shedding rate of zeolite is reduced from 1.02% of the raw gauze to 0.13% of the composite hemostatic gauze, and the in vitro coagulation time is reduced from 132 seconds of the raw gauze to 113 seconds of the composite hemostatic gauze, indicating that there is also a good synergistic effect between zeolite and halloysite.
[0153] Example 11: Animal Experiment
[0154] The zeolite gauze produced by Hangzhou Feichuang Life Science Co., Ltd. was selected as the raw material. The zeolite loaded on the zeolite gauze was P-type zeolite, and the zeolite loading was 15.6wt%. 0.75wt% styrene-butadiene latex was selected as the binder, and kaolin was coated on the zeolite gauze. The obtained product contained about 3.7wt% kaolin (see Figure 4 Figure (a) - Figure 4(d) in the figure). After coating, in vitro coagulation was reduced from 155 seconds to 139 seconds. The R value obtained by the thromboelastometry test was reduced from 3.2 minutes to 2.2 minutes. The powder shedding rate was reduced from 0.86% to 0.15%. In addition to this sample, ordinary medical absorbent cotton gauze, combat gauze from Z-Medica, USA, and zeolite gauze from Hangzhou Feichuang Life Science Co., Ltd. were also selected as reference samples. The hemostatic ability was tested using the rabbit femoral artery bleeding model ( Figure 5 ). The obtained data are shown in the following table:
[0155] Table 8
[0156]
[0157] From the above results, it can be seen that the composite hemostatic product (KZG) provided in this application has better hemostatic performance (short hemostatic time and less bleeding) and better safety (smaller powder shedding rate). It is worth noting that from the above results, it can be seen that the results obtained from the in vitro coagulation test may not be completely consistent with the results of the animal experiment. Among the four samples, pure absorbent cotton gauze does not contain hemostatic active substances, so it takes significantly longer time to achieve coagulation in both in vitro coagulation tests and animal experiments. The other three samples containing hemostatic active substances have significantly shorter hemostatic times in animal experiments. Interestingly, although combat gauze (CG) may be shorter than zeolite gauze and zeolite kaolin composite hemostatic gauze in in vitro coagulation tests, in animal experiments, zeolite gauze (ZG) and zeolite gauze with added kaolin (KZG) both gave shorter hemostatic times and less bleeding. The amount of bleeding in the KZG sample is only one-fourth of that of combat gauze, and the hemostatic time is only half of that of combat gauze. This indicates that hemostatic products with a higher zeolite content have better hemostatic effects in animal experiments when the in vitro coagulation indexes are similar. Figure 5 It can also be seen that after the hemostatic gauze is taken away after hemostasis, the wound cleanliness of the zeolite-kaolin composite hemostatic gauze after hemostasis is the highest, without a large amount of blood clots and powder residues, which is convenient for doctors to observe and handle later.
[0158] Figure 4 Figure (a) - Figure 4Figure (d) in the figure shows the SEM pictures of the original zeolite gauze and the KZG gauze coated with the kaolin-adhesive mixed coating. The spherical P-type zeolite crystals grow directly on the yarn surface of the zeolite absorbent gauze and are tightly combined without the participation of a binder. In the sample coated with the kaolin-adhesive mixed coating, it can be clearly observed that the kaolin-adhesive mixed coating is discontinuously covered on the zeolite gauze, and some areas of the zeolite crystals are covered, but some areas remain exposed. With the help of the adhesive, the kaolin is tightly and parallelly combined with the zeolite on the absorbent gauze. This special structure is also the reason why the product provided by the present invention has a special procoagulant performance.
[0159] Comparative Example 12:
[0160] S12-A: The zeolite gauze produced by in-situ synthesis technology provided by Hangzhou Feichuang Life Science Co., Ltd. is used as raw material. The zeolite loaded on the zeolite gauze is P-type zeolite, the calcium exchange rate of the zeolite is 67%, the gauze matrix is a mesh-patterned pure cotton non-woven fabric substrate, and the zeolite loading is 13.94wt%. The latex used in the configured slurry is carboxylated styrene-butadiene rubber, and the slurry contains 2.5wt% Y zeolite, and the latex concentration is 0.45wt%. In addition, 0.03wt% xanthan gum and 0.02% locust bean gum are used as suspending agents to improve the stability of the slurry. The slurry is coated on the zeolite gauze by dip coating, and the coating ratio is 1.6:1. After drying at 105℃, the zeolite-zeolite composite hemostatic gauze is obtained. The gauze contains 13.31wt% P zeolite, 3.82wt% Y zeolite, and the content of the self-adhesive component is 0.69wt%. The test results show that after coating, the zeolite shedding rate decreased from 0.91% of the raw gauze to 0.17% of the composite hemostatic gauze, and the in vitro coagulation time increased from 139 seconds of the raw gauze to 154 seconds of the composite hemostatic gauze. This shows that there is no significant synergistic effect between P zeolite and Y zeolite, and the self-adhesive-zeolite mixed coating reduces the powder shedding rate, but reduces the material's procoagulant ability.
[0161] S12-B: The synthesis steps are the same as S12-A, and the only changed condition is to replace the Y zeolite in the slurry with the same proportion of mesoporous silica SBA-15. The shedding rate of the obtained material is 0.16%, and the in vitro coagulation time is 167 seconds, which is significantly higher than the 139 seconds of the raw material zeolite gauze. This shows that there is no significant synergistic effect between zeolite and mesoporous silica. The self-adhesive-mesoporous silica mixed coating reduces the powder shedding rate, but reduces the material's procoagulant ability.
[0162] S12-C: The synthesis steps are the same as S12-A, and the only changed condition is to replace the Y zeolite in the slurry with an equal proportion of chitosan powder. The shedding rate of the obtained material is 0.29%, and the in vitro coagulation time is 162 seconds, which is significantly higher than the 139 seconds of the raw material zeolite gauze. This shows that there is no significant synergistic effect between zeolite and chitosan powder. The self-adhesive-chitosan mixed coating reduces the powder shedding rate, but reduces the material's procoagulant ability.
[0163] S12-D: The synthesis steps were the same as S12-A, and the only changed condition was to replace the Y zeolite in the slurry with an equal proportion of ochre powder. The shedding rate of the obtained material was 0.21%, and the in vitro coagulation time was 154 seconds, which was significantly higher than the 139 seconds of the raw zeolite gauze. This indicated that there was no significant synergistic effect between zeolite and ochre, and the self-adhesive-ochre mixed coating reduced the powder shedding rate, but reduced the material's procoagulant ability.
[0164] The above is a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.
Claims
1. A composite hemostatic gauze, characterized in that Including flexible zeolite gauze, kaolin-adhesive mixed coating; The flexible zeolite gauze comprises a flexible gauze base layer and zeolite, wherein the zeolite is directly nucleated and grown on the flexible gauze base layer by an in-situ growth technique, and the zeolite is directly connected to the flexible gauze base layer by a covalent bond; The kaolin-self-adhesive mixed coating is formed by uniformly mixing kaolin or kaolin-like minerals and a binder, coating the mixture on the flexible zeolite gauze, and then drying the mixture; the kaolin-self-adhesive mixed coating covers the flexible gauze substrate and part of the zeolite surface, but does not exist between the zeolite and the flexible gauze substrate; The weight ratio of the zeolite to kaolin or kaolin-like mineral is 1.5:1-10:
1.
2. A composite hemostatic gauze according to claim 1, characterized in that: The weight ratio of the adhesive to the composite hemostatic gauze is 0.4%-1.2%; the adhesive adopts an aqueous polymer latex diluent, and the aqueous polymer latex diluent includes polymer latex particles dispersed in water; the glass transition temperature Tg of the polymer latex particles is ≤25°C.
3. A composite hemostatic gauze according to claim 2, characterized in that: The polymer latex particles include one or more of chloroprene rubber, styrene butadiene rubber, carboxylated styrene butadiene rubber, polyurethane, pure acrylic rubber, styrene acrylic rubber, polyacrylate rubber, and oxidized polyethylene, and have a diameter of 50-500 nanometers; the kaolin-like mineral is halloysite or halloysite.
4. A method for preparing a composite hemostatic gauze according to any one of claims 1 to 3, characterized in that The following steps are included: Step 1: preparing a flexible zeolite gauze by an in-situ synthesis method; wherein the flexible zeolite gauze is formed by directly connecting the zeolite and the flexible gauze substrate via a covalent bond, and has nothing to do with the self-adhesive coating; Step 2: preparing a mixed slurry of kaolin or kaolin-like minerals and a binder; the weight content of kaolin in the mixed slurry is 0.50%-5.0%; Step 3: evenly coating the mixed slurry obtained in step 2 on the zeolite gauze; Step 4: drying the zeolite gauze coated with the mixed slurry at 70-120° C. to obtain a finished zeolite-kaolin composite hemostatic gauze.
5. The method according to claim 4, characterized in that The zeolite in the flexible zeolite gauze in step one is at least one of P-type zeolite, A-type zeolite, X-type zeolite, Y zeolite and CHA zeolite; the flexible gauze substrate is various materials with flexible cloth form, including cotton cloth, absorbent cotton gauze, absorbent cotton non-woven fabric, polyvinyl alcohol gauze, polyurethane non-woven fabric, and cloth blended with multiple fibers.
6. The method according to claim 4 or 5, characterized in that In step 1, the cations of the zeolite in the flexible zeolite gauze contain at least one of calcium ions, silver ions, zinc ions, and copper ions, wherein the molar amount ratio of the calcium ions is 5-99%.
7. The method according to claim 4, characterized in that Step 2 specifically comprises diluting the binder with water to form a binder diluent having a solid content of 0.20wt%-0.80wt%; adding kaolin or kaolin-like mineral powder to the binder diluent, adjusting the pH to between 7.0-10.0, and stirring to obtain a stably dispersed mixed slurry; the binder adopts an aqueous polymer latex diluent, which is composed of polymer latex particles and water as a dispersant; the polymer latex particles are negatively charged or non-ionic.
8. The method according to claim 4, characterized in that The weight loading amount of zeolite in the zeolite gauze material in step 1 is 5%-30%; the weight ratio of the mixed slurry and the flexible zeolite gauze in step 3 is 1:1-4:1.
Citation Information
Patent Citations
A molecular sieve / fiber composite material and its preparation method
CN109851858B
Slurry for coating hemostatic gauze and hemostatic gauze prepared using the slurry
CN115990284B
Zeolite hemostatic gauze material and preparation method thereof
CN116036343A
Zeolite tourniquet bandage
CN102366640A